Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Kemampuan Berpikir Kritis Pada Materi Sistem Pencernaan Di Kelas XI Sma Negri 1 Stabat - Haryati Haryati; Tedy Putra; Ade Evi Fatimah; Diah Kesumawati (Keguruan, 2020)
This study aims to determine the effect of Problem Based Learning on students' critical thinking skills in grade XI of SMA Negeri 1 Stabat. This study uses a quasi-experimental research type and the design which is used one quivalent (Pretest and Posttest) Control-Group Design. The research method which is usedÂ  the experimental method using two classes, namely the experimental and control classes. The significance value obtained is 0.000 0.05 so it can be concluded that Ho is rejected and Hi is accepted. The results showed that there was an effect of the Problem Based Learning (PBL) learning model on students' critical thinking skills and was effective for improving several indicators of students' critical thinking skills in the Digestive System subject in grade XI of SMA Negeri 1 Stabat.